Pembelajaran Pendidikan Agama Islam berdasarkan pendekatan logis untuk meningkatkan pikiran kritis dan motivasi berprestasi di SMK Kita Bhakti dan SMK Raden Fatah Mojosari - Syu'aib Nawawi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Science given by God to man through his brain an integral part of the values of divinity as essential sources of knowledge, is of God. Apart from the paradigm that reduces intuition and metaphysical things, al-Qur'an as unceasingly called for people to continue reviewing, researching, studying, thinking and examine all of the phenomena that exist, because nothing in this world that is created in vain. The motivation given, is nothing for man to know and realize the power of his mind in order to add to the faith in God. Fortunately models such as the way of thinking so that the characteristics of 2013. The curriculum is a danger that a scientific approach that uses the methods of scientific thinking stands by itself without any control limit values contained wise in religion (Islam). Make learning Islamic education students based on a logical approach to improve critical thinking and motivation of achievement in SMK and SMK Bhakti We Raden Patah Mojosari be an interesting learning model and help teachers to improve learning effectiveness. This study used a qualitative approach through case studies. Researchers conducted this study to determine